Effect of supplementing tropical tannin-free and tanniniferous legumes to grass-fed sheep on the utility of their manure as nitrogen fertiliser - Tiemann, Tassilo T.; Hincapié Carvajal, Belisario; Frossard, Emmanuel; Kreuzer, M.; Hess, H.D. (2009)
A pot experiment was conducted to assess the fertiliser value of faeces from sheep fed with a diet supplemented with legumes free of or containing condensed tannins. Ten animals received the same five diets in different experimental runs of a double Latin Square design, all consisting of a low quality tropical grass ration, supplemented with 450g/kg legumes. Legume treatments were either solely Vigna unguiculata (a tannin free herbaceous legume) or mixtures of V. unguiculata with either Calliandra calothyrsus or Flemingia macrophylla (both shrub legumes rich in condensed tannins) in ratios of 2:1 and 1:2. Faeces from animals receiving the same diets were pooled and applied at two levels (20 and 80 mg N/kg soil) to pots with seedlings from the cultivar Mulato II, a Brachiaria grass hybrid. An acidic infertile tropical soil was used. Aerial biomass yield and plant N content were evaluated.